Thermal conductivity and acoustic properties of natural fiber mixed polyurethane composites - (:unkn) unknown (My University, 2011)
Natural cotton, bamboo and wool fibers were used as reinforcement agents in a polyurethane-based matrix to improve the sound absorption and thermal conductivity properties of the composite. Generally, adding cotton, bamboo or wool fibers to polyurethane foam, improves its sound absorption coefficient. In this study, cotton fibers were observed to provide the best sound absorption coefficient. At higher frequencies, increasing the bamboo or wool fiber content decreases the sound absorption coefficient for the composite. Adding cotton, wool or bamboo fibers to polyurethane foam does not result in a significant change in the thermal conductivity of the material. The best thermal conductivity value was observed with a composite including 4% cotton fiber.
Keywords: Composites; Natural fiber; Polyurethane; Sound absorption; Thermal properties